STUDIES ON THE PENETRATION AND VIABILITY OF SOME PATHOGENIC BACTERIA IN TABLE EGGS; (1) FOLLOWING UP SURVIVAL OF E. coli, Proteus vulgaris AND Pseudomonas aeruginosa INSIDE THE EGG. - S. R. AL -Obaidi , A. (The Iraqi Journal of Veterinary Medicine, 1994)
Laboratory experiments were done to study the possible circumstances which might accompany some pathgenic bacterial species which penetrate table eggs, being contaminated either naturally or experimentally. In the first stage, the contents (albumin + yolk) of each of 28 eggs were cultured directly onto brain heart-infusion (BHI), brilliant green sulfa (BGS), MacConkey Agar (MA), mannitol salt agar (MSA), tellurite blood agar (TBA) and 5% sheep blood agar (SBA); in addition to selenite broth (SB). Out of 28 egg samples, 8 bacterial isolates were recovered and identified; as 4 Staphylococcus aureus, 2 Bacillus subtilis and 2 Proteus vulgaris. In the second stage, another 28 eggs were artificially contaminated by calibrated doses of each of E. coli, Pr. vulgaris and Ps. aeruginosa which were originally isolated from different disease conditions in children. Contamination of each egg was carried out as spots (droplets) on certain areas on the surface. Preliminary results showed a successful penetration of the organisms through the egg within 10, 15 and 30 minutes, and also after 2 and 4 hrs of storage at temperature (12-18 °C), although their numbers were decreasing progressively, espically within the egg’s contents, until they could not be recovered after 8 days of storage.